2014
DOI: 10.1001/jamapediatrics.2013.5070
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Benefits of an Early Online Problem-Solving Intervention for Executive Dysfunction After Traumatic Brain Injury in Children

Abstract: IMPORTANCE Executive dysfunction after traumatic brain injury (TBI) in children is common and leads to significant short- and long-term problems in functioning across multiple settings. We hypothesized that improvements in short-term executive function would be maintained to 24 months after injury and that improvements would increase over time in a counselor-assisted problem-solving (CAPS) intervention. OBJECTIVE To evaluate the efficacy of a CAPS intervention administered within 7 months of complicated mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 44 publications
0
44
0
1
Order By: Relevance
“…Clinical trials of mood stabilizers are very difficult to accomplish, especially for children with PC, but should be done. Cognitive rehabilitation targeting processing speed, attention, problem solving, and memory may enhance cognitive control (a form of executive function) over emotional expression and should be tested 39 . It is conceivable that more specific emotional probes such as utilized in social cognition and affect recognition studies will further clarify important mechanisms in children with PC and possibly other disorders of affective dysregulation 34,36,40-42 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of mood stabilizers are very difficult to accomplish, especially for children with PC, but should be done. Cognitive rehabilitation targeting processing speed, attention, problem solving, and memory may enhance cognitive control (a form of executive function) over emotional expression and should be tested 39 . It is conceivable that more specific emotional probes such as utilized in social cognition and affect recognition studies will further clarify important mechanisms in children with PC and possibly other disorders of affective dysregulation 34,36,40-42 .…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Tele-health treatments may benefit adolescents after TBI. [5][6][7][12][13][14][15]20 However, meta-analyses comparing online to traditional face-to-face approaches for various psychiatric and medical conditions have yielded mixed conclusions. 14,21,22 Although some reviews indicated comparable efficacy of traditional and tele-health interventions, 22 others noted smaller effects for online treatments.…”
Section: Pediatrics Volume 135 Number 2 February 2015mentioning
confidence: 99%
“…The structured interview and parent-reported measures were completed at baseline and again immediately after treatment (6 months postbaseline) and at 12 and 18 months postbaseline. 20 Participants were randomly assigned to the following groups: (1) Counselor-Assisted Problem Solving (CAPS), a 6-month Web-based, therapist-moderated intervention providing training in problem-solving, communication, and self-regulation, or (2) IRC, a control intervention providing self-guided, Web-based TBI information and resources. Randomization was stratified according to race and gender.…”
Section: Baseline and Follow-up Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Researchers are also exploring ICBT for youth, but research on efficacy is limited. [15, 16] Other internet programs have been shown to improve outcomes in the management of conditions such as headache, back pain, tinnitus, urinary stress incontinence, smoking cessation, and medication adherence in adults[1720], and encopresis[21], traumatic brain injury[22], diabetes management[23, 24], eating disorders[25], and prevention of high risk behaviors[26, 27] in youth.…”
Section: 0 Introductionmentioning
confidence: 99%